Level of Knowledge and Attitude of Waste Management in Faculty of Public Health Students UIN Sumatera Utara Medan - Yulia Khairina Ashar (UIN Sumatera Utara Medan, 2020)
The issue of environmental protection has reached the highest importance in the current global era, but in practice the basic concepts of waste management are often ignored. In this case everyone has the knowledge of the management of waste but in its application be negative or bad. The study was conducted to determine the relationship of the level of knowledge with the attitude of waste management in FKM UIN Sumatera Utara Medan students. This study used a cross-sectional design with a sample of 245 students. Sampling was done using 2 methods. In the first method, samples are taken using Cluster Sampling with the PPS (Probability Proportionate to Size) technique, then the second method is taken using Simple Random Sampling. Inclusion criteria were students who were willing to be respondents of the study and were present during the study and the exclusion criterion were students who resigned and were not present during the study. Analysis of the data used is univariate and bivariate analysis. The results of the analysis of the relationship between the level of knowledge with a good attitude of waste management showed that there were 141 (61.3%) students who had good knowledge of being good in carrying out waste management. While among students who have poor knowledge, there are 11 (73.3%) students who behave well in managing waste. so, there is no significant relationship between the level of knowledge with the attitude of waste management in FKM UIN North Sumatra Medan students.